Human AATF/Che-1 forms a nucleolar protein complex with NGDN and NOL10 required for 40S ribosomal subunit synthesis - Bammert, Lukas (Nucleic Acids Res, 2016)
Mammalian AATF/Che-1 is essential for embryonic development, however, the underlying molecular mechanism is unclear. By immunoprecipitation of human AATF we discovered that AATF forms a salt-stable protein complex together with neuroguidin (NGDN) and NOL10, and demonstrate that the AATF-NGDN-NOL10 (ANN) complex functions in ribosome biogenesis. All three ANN complex members localize to nucleoli and display a mutual dependence with respect to protein stability. Mapping of protein-protein interaction domains revealed the importance of both the evolutionary conserved WD40 repeats in NOL10 and the UTP3/SAS10 domain in NGDN for complex formation. Functional analysis showed that the ANN complex supports nucleolar steps of 40S ribosomal subunit biosynthesis. All complex members were required for 18S rRNA maturation and their individual depletion affected the same nucleolar cleavage steps in the 5′ETS and ITS1 regions of the ribosomal RNA precursor. Collectively, we identified the ANN complex as a novel functional module supporting the nucleolar maturation of 40S ribosomal subunits. Our data help to explain the described role of AATF in cell proliferation during mouse development as well as its requirement for malignant tumor growth.